A new species of Hechtia (Bromeliaceae; Hechtioideae) from the state of Morelos, Mexico - González-Rocha, Edith; López-Ferrari, Ana Rosa; Cerros-Tlatilpa, Rosa; Espejo-Serna, Adolfo (Instituto de Ecología, A.C., 2014)
Hechtia montis-frigidi, a new species from Morelos, Mexico is described and illustrated. The new taxon is compared with H. chichinautzensis and H. podantha, species with similar characteristics.